Extraction of stem oils from Cinnamomum cassia and NMR characterization to produce nutraceuticals - RAMOS, Vitor Santos; MERAT, Pedro Paulo; IULIANELLI, Gisele; SILVA, Eduardo Miguez; BELLO, Thiago Muller Herdy; TAVARES, Maria Inês Bruno (Food Science and Technology, 2023)
Functional foods offer health benefits as a function of their bioactive compounds, beyond their basic nutritional functions. They can, for example, reduce the risk of chronic degenerative diseases such as cancer, diabetes, and cardiovascular damage, among others. Nutraceuticals can be produced using the bioactive compounds present in these foods. Essential oils are used according to the need and/or specific characteristics of their active ingredients. The objective of this study was to extract essential oil from the stem of Cinnamomum cassia by hydrodistillation employing the Clevenger apparatus. The results show the extraction of a dense yellow oil. This oil was characterized by solution nuclear magnetic resonance using the 1H and 13C nuclei. The results showed a correlation in 92% of cinnamaldehyde. The nutraceutical containing this oil was obtained from the nanoprecipitation process, generating a nanoencapsulation of the oil in the polycaprolactone. This new material was characterized by scanning electron microscopy. The micrography showed the homogeneous nanostructure of the nanoencapsulated material.